Diversi dalam Kerangka Restorative Justice pada Penanganan Anak yang Berhadapan dengan Hukum - Riyadi Riyadi (Syntax Corporation Indonesia, 2023)
Clinical Pathways is a measurement tool for hospitals to deliver health services in maintaining quality and monitoring costs. Dengue fever is a tropical infectious disease with typical symptoms that should have standardized treatment patterns. However, in RSIA Kenari Graha Medika, the treatment of dengue fever cases is considered not efficient and effective enough. This study aims to determine the compliance rate in the implementation of Clinical Pathway for pediatric patients with a diagnosis of Dengue Fever at RSIA Kenari Graha Medika. The method used was qualitative with descriptive observational using Clinical Pathway compliance form data from medical records and hospital information systems from September 2022 to February 2023. Inclusion criteria were pediatric patients who were treated with a single diagnosis of Dengue Fever in accordance with WHO clinical criteria, namely Fever, Malaise, Peripheral bleeding disorders and had laboratory examination results with Platelet values below 100,000 / mm3. The things that are assessed in Clinical Pathways compliance are length of stay, administration of therapy and supporting examinations. Based on the results of the study LOS has no influence on clinical pathway. Meanwhile, pharmacy and lab showed that pharmacy and lab had a positive and significant effect on clinical pathway. It is hoped that there will be further research related to this study, namely looking for the relationship of the lack of compliance rates with the costs incurred during treatment.